Comparative of Stock Prices and Returns Before and After the Stock Split in Companies Listed on the Indonesia Stock Exchange for the Period 2010 to 2015 - Muhammad Budi; Kiki Farida Ferine; Suwarno (Britain International for Academic Research (BIAR) Publisher, 2022)
Corporate actions such as stock splits may have a mixed effect on stock price fluctuations and investors' projected returns. As such, this research aims to ascertain the difference in stock prices and returns in firms listed on the Indonesian Stock Exchange before preceding and after the stock split. Purposive sampling was used to choose the sample for this study. The study sample was chosen based on firms that split their stocks between 2010 and 2015, and we received data on up to 35 companies. The descriptive statistics and hypothesis testing were studied in this research. The paired sample t-test findings indicate that there was no significant difference in stock returns between 2010 and 2015 for companies listed on Indonesian Stock Exchange. In other words, the lack of this difference is more likely attributable to the market anticipating a higher average return before to the news of the stock split than the average stock return after the announcement of the stock split.